The Studi Bibliometrika pada Abstrak Artikel Bidang Ilmu Sosiologi Periode 2015-2018 - Rhoni Rodin; Nur Afifah (UPT Perpustakaaan Universitas Hasanuddin, 2019)
This study examines articles of sociology using bibliometric studies. A bibliometric study of this article is important to determine the development of sociology. This study aims to determine obsolescence, half-life, and to find out the results of ZIPF's postulate for 2015-2018. This research is a quantitative descriptive study using a bibliometric study. The sampling technique used purposive sampling so that the number of samples obtained was 10 articles in 2015-2018. The results showed that the half life in the Sociology article was the highest, which was 24 years, and the zipf postulate of this Sociology article with the highest word ranking, namely the 11th rank of the article entitled Adolescent Behavior Using Gadgets: Sociological Analysis of Educational Theory.